Exploring biochar and fishpond sediments potential to change soil phosphorus fractions and availability - Mahmood, Mohsin; Wang, Yunting; Ahmed, Waqas; Mehmood, Sajid; Ayyoub, Anam; Elnahal, Ahmed S. M.; Li, Weidong; Zhan, Xin (Frontiers in Plant Science, 2023)
Phosphorus (P) availability in soil is paradoxical, with a significant portion of applied P accumulating in the soil, potentially affecting plant production. The impact of biochar and fishpond sediments as fertilizers on P fixation remains unclear. This st udy aimed to determine the optimal ratio of biochar (BR), modified biochar (MBR), and fishpond sediments (FPS) as fertilizer replacements. A pot experiment with maize evaluated the transformation of P into inorganic (Pi) and organic (Po) fractions and thei r contribution to P uptake. Different percentages of FPS, BR, and MBR were applied as treatments (T1 to T7), T1 [(0.0)], T2 [(Fish pond sediments 25.0%)], T3 [(Fish pond sediment 25.0 %+ Biochar 1%)], T [(FPS (25%) +MBR (3%)], T5 [(FPS 35%),] T6 [FPS (35%)+BR(1%)] and T7 [FPS(35%)+MBR(1%)]. Using the modified Hedley method and the Tiessen and Moir fractionation scheme, phosphorus fractions were determined. Results showed that various rates of MBR, BR, and FPS significantly increased labile and moderately labile P fractions (NaHCO3-Pi, NaHCO3-Po, HClD-Pi, and HClC-Pi) and residual P fractions compared to the control (T1). Positive correlations were observed between P uptake, phosphatase enzyme activity, and NaHCO3-Pi. Maximum P uptake and phosphatase activity were observed in T6 and T7 treatments. The addition of biochar, modified biochar, and fishpond sediments increased Po fractions. Unlike the decline in NaOH -Po fraction, NaHCO3-Po and HClc-Po fractions increased. All Pi fractions, particularly apatite (HClD-Pi), increased across the T1 to T7 treatments. HClD-Pi was the largest contributor to total P (40.7%) and can convert into accessible P over time. The T5 treatment showed a 0.88% rise in residual P. HClD-Pi and residual P fractions positively correlated with P uptake, phosphatase activity, NaOH-Pi, and NaOH-Po moderately available fractions. Regression analysis revealed that higher concentrations of metals such as Ca, Zn, and Cr significantly decreased labile organic and inorganic P fractions (NaHCO3-Pi, R 2 = 0.13, 0.36, 0.09) and their availability (NaHCO3-Po, R 2 = 0.01, 0.03, 0.25). Excessive solo biochar amendments did not consistently increase P availability, but optimal simple and modified biochar increased residual P contents in moderately labile and labile forms (including NaOH-Pi, NaHCO3-Pi, and HClD-Pi).